2017
DOI: 10.3892/etm.2017.4513
|View full text |Cite
|
Sign up to set email alerts
|

miR-16-1 expression, heat shock protein 70 and inflammatory reactions in astrocytes of mice with epilepsy induced by encephalitis B virus infection

Abstract: The upregulation of miR-16-1 expression and heat shock protein 70 (HSP70) and inflammatory reaction mechanism in astrocytes of mice with epilepsy induced by encephalitis B virus infection were studied. Six-to-eight-week-old healthy male C57BL/6 mice received intraperitoneal injection of pilocarpine (320–340 mg/kg, 40 mg/ml) to induce status epilepsy. After 7 days, mice were inoculated with 100 µl Dulbecco's modified Eagle's medium (DMEM) in the neck, including 6.25×23 PFU Japanese encephalitis virus P3 wild st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…For instance, overexpressed miR‐124a reduced the expression of MCP‐1, miR‐16 suppressed the epithelial‐mesenchymal transition (EMT) induced by TGF‐β1 in non–small‐cell lung carcinoma cells (NSCLC) and miR‐16 decreased the expression of TNF by Bcl‐2 in liver failure. 30 , 31 , 32 Additionally, increased miR‐16‐1 and TNF‐α expression has been detected in the astrocytes of epilepsy mice, 33 which although contradictory to the findings of our study, emphasized the regulatory role of miR‐16 and TNF‐α.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, overexpressed miR‐124a reduced the expression of MCP‐1, miR‐16 suppressed the epithelial‐mesenchymal transition (EMT) induced by TGF‐β1 in non–small‐cell lung carcinoma cells (NSCLC) and miR‐16 decreased the expression of TNF by Bcl‐2 in liver failure. 30 , 31 , 32 Additionally, increased miR‐16‐1 and TNF‐α expression has been detected in the astrocytes of epilepsy mice, 33 which although contradictory to the findings of our study, emphasized the regulatory role of miR‐16 and TNF‐α.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the study of IL-6-deficient mice, IL-6 plays a role as a neuroprotective factor in epileptic brain injury [49]. Furthermore, IL-6 and TNF-α were also selected as representatives of inflammatory injury in epileptic rats [50]. Therefore, this study also detected the expression of inflammatory factors IL-6 and TNF-α in epileptic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Yao et al showed that the expression of miR-16-1 and heat shock protein 70 was upregulated in astrocytes during the occurrence of epilepsy after JEV infection [16]. Another case report led by Ma et al showed that JEV infection can trigger anti-N-methyl-Daspartate receptor encephalitis [17].…”
Section: Further Informationmentioning
confidence: 99%